Associations between psychological distress and hair cortisol during pregnancy and the early postpartum: A meta-analysis. (January 2023) - Khoury, Jennifer E.; Giles, Lauren; Kaur, Hargun; Johnson, Dylan; Gonzalez, Andrea; Atkinson, Leslie
Abstract: Pregnancy and the early postpartum signify a period of high stress. Perinatal stress can include psychological distress (PD), such as anxiety, depression, and stress, as well as neuroendocrine stress, indexed by activation of the hypothalamic-pituitary-adrenal (HPA) axis and the production of the hormone cortisol. Elevated PD and cortisol levels during the perinatal period can have long-term implications for the mother and child. Methodological advances have enabled the sampling of cortisol from hair, to provide a retrospective marker of HPA axis activity over several months. Despite knowing that maternal PD and HPA activity during the perinatal period independently impact health and development, research to date is unclear as to the association between maternal PD and hair cortisol. The present meta-analysis included 29 studies to assess the strength of the relation between maternal PD and hair cortisol levels during pregnancy and the early postpartum period. Several sample and methodological factors were assessed as moderators of this effect. Analyses were conducted using multilevel meta-analysis. Results of the multilevel meta-analysis indicated that the overall effect size between PD and HCC was small but not significant z  = 0.039, 95% CI [− 0.001, 0.079]. Moderator analyses indicated that the strength of the association between PD and hair cortisol was moderated by pregnancy status (i.e., effects were stronger in pregnant compared to postpartum samples), timing of HCC and PD measurements (i.e., effects were larger when PD was measured before HCC) and geographic location (i.e., effects were larger in North American studies). The findings advance our understanding of the link between PD and HPA activity during the perinatal period, a time of critical impact to child development. Highlights: Meta-analysis found a small (non-significant) association between perinatal psychological distress (PD) and hair cortisol. There is significant heterogeneity in the effect between PD and hair cortisol. PD and hair cortisol effects moderated by perinatal stage, timing of PD and hair cortisol measures, and article characteristics.